Impact of Coxiella burnetii vaccination on humoral immune response, vaginal shedding, and lamb mortality in naturally pre-infected sheep - Bauer, Benjamin Ulrich; Schoneberg, Clara; Herms, Thea Louise; Kleinschmidt, Sven; Runge, Martin; Ganter, Martin (Frontiers in Veterinary Science, 2022)
Sheep are considered to be one of the main reservoirs for Coxiella burnetii, a gram-negative bacterium with high zoonotic potential. Infected sheep shed tremendous amounts of the pathogen through birth products which caused human Q fever epidemics in several countries. Information about the impact of an inactivated C. burnetii Phase I vaccine on humoral immune response, vaginal shedding, and lamb mortality in naturally pre-infected sheep is scarce. Therefore, two identically managed and naturally C. burnetii-infected sheep flocks were examined for two lambing seasons (2019 and 2020). One flock (VAC) received a primary vaccination against Q fever before mating and the second flock served as control (CTR). In each flock, one cohort of 100 ewes was included in follow-up investigations. Serum samples at eight different sampling dates were analyzed by C. burnetii phase-specific ELISAs to differentiate between the IgG Phase I and II responses. Vaginal swabs were collected within three days after parturition and examined by a C. burnetii real-time PCR (IS1111). Lamb losses were recorded to calculate lamb mortality parameters. After primary vaccination, almost all animals from cohort VAC showed a high IgG Phase I response up until the end of the study period. In cohort CTR, the seropositivity rate varied from 35.1 % to 66.3 %, and the Phase I and Phase II pattern showed an undulating trend with higher IgG Phase II activity during both lambing seasons. The number of vaginal shedders was significantly reduced in cohort VAC compared to cohort CTR during the lambing season in 2019 (p<0.0167). There was no significant difference of vaginal shedders in 2020. The total lamb losses were low in both cohorts during the two investigated lambing seasons (VAC 2019: 6.8 %, 2020: 3.2 %; CTR 2019: 1.4 %, 2020: 2.7 %). Therefore, neither the C. burnetii vaccine nor the C. burnetii infection seem to have an impact on lamb mortality. Taken together, the inactivated C. burnetii Phase I vaccine induced a strong IgG Phase I antibody response in naturally pre-infected sheep. It might also reduce vaginal shedding in the short term but seems to have little beneficial impact on lamb mortality.